Evaluation of Waste Management in XYZ University Area in Yogyakarta - Hidayat, Salsabila; Yuriandala, Yebi (Applied Research in Science and Technology, 2024)
The increasing volume of waste is driven by several factors, including population growth, urbanization, and changes in lifestyle. This rise in waste generation has outpaced the capacity of available landfill space, leading to the improper accumulation of unmanaged waste. This study aims to evaluate the current waste management practices, analyze the waste generation and composition, and propose an effective waste management scenario. A quantitative descriptive analysis approach was employed, utilizing waste generation and composition data measured in accordance with the Indonesian National Standard (SNI) 19-3964-1994. The proposed waste management scenario is aligned with the guidelines outlined in Sleman Regency Regulation No. 4 of 2015. The operational techniques for managing waste include stages such as storage, collection, transportation, and treatment, which are outsourced to a third party. The findings of this study indicate that the waste at eight sampling points averaged 359,250 kg/day and 4,058 m³/day. The waste composition is predominantly organic (2.48%), paper and cardboard (12.4%), and other types of waste (11.07%). The proposed processing methods focus on utilizing technologies for organic waste and residue treatment, such as Masaro technology.